Visualizing the interfacial-layer-based epitaxial growth process toward organic core-shell architectures - Ming-Peng Zhuo; Xiao Wei; Yuan-Yuan Li; Ying-Li Shi; Guang-Peng He; Huixue Su; Ke-Qin Zhang; Jin-Ping Guan; Xue-Dong Wang; Yuchen Wu; Liang-Sheng Liao (Nature Communications, 2024)
Abstract Organic heterostructures (OHTs) with the desired geometry organization on micro/nanoscale have undergone rapid progress in nanoscience and nanotechnology. However, it is a significant challenge to elucidate the epitaxial-growth process for various OHTs composed of organic units with a lattice mismatching ratio of > 3%, which is unimaginable for inorganic heterostructures. Herein, we have demonstrated a vivid visualization of the morphology evolution of epitaxial-growth based on a doped interfacial-layer, which facilitates the comprehensive understanding of the hierarchical self-assembly of core-shell OHT with precise spatial configuration. Significantly, the barcoded OHT with periodic shells obviously illustrate the shell epitaxial-growth from tips to center parts along the seeded rods for forming the core-shell OHT. Furthermore, the diameter, length, and number of periodic shells were modulated by finely tuning the stoichiometric ratio, crystalline time, and temperature, respectively. This epitaxial-growth process could be generalized to organic systems with facile chemical/structural compatibility for forming the desired OHTs.